The identification of hydrogen embrittlement and the role of intergranular brittle fracture of API 5DP G105 drill pipe failure on onshore drilling activity - Aribowo, Sidhi; Soedarsono, Johny Wahyuadi; Suryadi, Suryadi; Nurhadi, Slamet; Warneri, Warneri; Simanullang, Sopar Mangarapot; Kaban, Agus; Kamila, Raajwa Ayudhia (Eastern-European Journal of Enterprise Technologies, 2026)
The object of this study is high-strength steel of API 5DP Gr 105 that has been used during well completion in a corrosive environment. This work emphasizes key factors affecting material damage caused by slip marks, tensile load, and hydrogen content in contaminated brine and completion fluid, which were not addressed in previous studies. Several tests, including chemical, mechanical, and surface characterization, were conducted. The chemical composition test of the fluid shows that the brine has been contaminated by H2S gas and sulfur, with inevitable traces of chloride, bicarbonate, carbonate, bisulfide, and sulfide, providing active sites for hydrogen atom diffusion at the slip marks. The material composition test confirms that the failed material is API 5DP Gr 105. A noticeable amount of phosphorus increases grain boundary segregation and weakens the cohesive metallic bond. A hardness at 28 Rockwell C is inevitable and increases the material’s vulnerability to embrittlement, despite the Charpy energy test showing a manageable level, confirming local brittleness. The high tensile strength of 914 MPa is evidence of embrittlement, even though the material remains ductile, with a noticeable elongation of 20%. An intergranular crack was observed in the microstructure, and slip marks serve as stress concentrators for the crack. Thus, it can be concluded that the combination of tensile load, hydrogen gas content, local slip marks, and completion fluid in the well weakened the grain boundaries and served as an initial crack with a high hydrogen-atom concentration. This work models the root-cause analysis of high-strength steel during well-completion operations in an onshore facility